Growth monitoring still has a place in selected populations of children. (28th March 2011) - Hussain, M; John, C M; Mohamed, K; Zbaeda, M; Ng, S M; Chanderasekaran, S; Didi, M; Blair, J C
Abstract : In 1998, a multiprofessional group developed a consensus on growth monitoring in the UK. While routine serial measurements were not recommended in healthy children, it is clear that there is a subset of children at increased risk of growth-modifying disease who may benefit from growth monitoring. This subset includes children with genetic disorders at increased risk of thyroid dysfunction. Symptoms and signs of thyroid dysfunction are non-specific in the early stages of disease and are easily mistaken for features of an underlying genetic disorder. In this article, we report the case of a 2.8-year-old girl with 18q deletion syndrome who was profoundly weak, hypotonic and poorly responsive at diagnosis of Grave's disease. She was tall and her bone age was 2 years advanced, indicating long-standing disease. Growth monitoring of this patient should have enabled earlier diagnosis and avoided a serious and potentially fatal episode.